2019
DOI: 10.2306/scienceasia1513-1874.2019.45.515
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the gut microbiome in red deer (Cervus elaphus) and fallow deer (Dama dama) by high-throughput sequencing of the V3-V4 region of the 16S rRNA gene

Abstract: Comparison of the gut microbiome in red deer (Cervus elaphus) and fallow deer (Dama dama) by high-throughput sequencing of the V3-V4 region of the 16S rRNA gene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…Firmicutes has been reported as the most frequent phylum in fecal samples of cattle, horses (2,31,32) , and red deer (33) . This abundance is related to high fiber intake (34) . Verrucomicrobia was the second abundant phylum in the cattle samples in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Firmicutes has been reported as the most frequent phylum in fecal samples of cattle, horses (2,31,32) , and red deer (33) . This abundance is related to high fiber intake (34) . Verrucomicrobia was the second abundant phylum in the cattle samples in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The gut microbiome can provide energy, in the form of short-chain fatty acids, to its host and maintain the gut homeostatic balance ( Gonçalves et al, 2018 ; Markowiak-Kopeć and Śliżewska, 2020 ). Many factors affect gut microbiome composition and function, including diet ( Huang et al, 2022 ), phylogeny ( Wang et al, 2019 ; Gregor et al, 2022 ), and environment ( Gacesa et al, 2022 ; Wang et al, 2022 ). When a factor surpasses the other influencing factors, the gut microbiome converges to adapt toward this dominant factor.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome is an important factor for host adaptations to the environment (Wang et al, 2019 ; Wang, Shang, Wei, et al, 2022 ; Wang, Shang, Wu, et al, 2022 ; Wang, Wu, et al, 2022 ). Wang, Shang, Wu, et al ( 2022 ) found that the gut microbiome function of red and corsac foxes can help hosts adapt to different environmental niches.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to adapt to plateau environments, short‐chain fatty acid (SCFA)‐producing bacteria are significantly enriched in the host gut (Li et al, 2016 ; Zhang et al, 2016 ). The gut microbiome also plays an important role in host health and survival (Davies et al, 2022 ; Gentile & Weir, 2018 ) and is dependent on various factors, such as diet (Greene et al, 2020 ; Wu et al, 2022 ), phylogeny (Sun et al, 2021 ; Wang et al, 2019 ), and habitat (Gacesa et al, 2022 ). Previous studies have shown that mammal gut microbiomes are strongly correlated with host phylogeny (Amato et al, 2019 ; Ley et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%